Systematic Review: Anticancer Activity of Chromolaena odorata L. - Rivaldi Sitinjak; Marina Silalahi; Fajar Adinugraha (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Cancer is one of the leading causes of death in the world, and conventional therapies such as chemotherapy and radiotherapy often cause significant side effects. Therefore, natural ingredients are a promising alternative, one of which is Chromolaena odorata, which is known to be rich in flavonoids, alkaloids, and terpenoids. This study aims to systematically review the evidence of anticancer activity of C. odorata based on in vitro and in vivo studies. The literature review was conducted through PubMed, ScienceDirect, Google Scholar, and Web of Science databases using the PRISMA 2020 method, and ten articles were obtained that met the inclusion criteria. The analysis showed that C. odorata extracts and fractions have cytotoxic activity against various cancer cell lines, including breast (MCF-7, T47D, MDA-MB-231, 4T1), cervical (HeLa), liver (HepG2), colon (HT-29, WiDr, HTB), and skin keratinocyte models (HaCaT). The identified mechanisms include induction of apoptosis, arrest of the G₀-G₁ phase of the cell cycle, suppression of proliferation, and modulation of apoptosis-regulating protein expression. Kaempferide compounds emerged as the most potent candidates with low toxicity to normal cells. However, differences in the extraction method, dose, and cell type led to variations in effectiveness, and the combination with cisplatin on MDA-MB-231 cells showed antagonistic effects. Thus, C. odorata has great potential to be developed as a complementary therapy as well as a source of new lead compounds, although further research is needed to evaluate bioavailability, pharmacokinetics, and safety through preclinical and clinical trials.